Value of Ultrasound in the Diagnosis of Cholecystitis - Ngoc, Doan Van; Quyet Thang, Tran; Cong Hoan, Tran; Van Sang, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2022)
Abstract: This study was carried out on 64 patients with a preoperative diagnosis of cholecystitis and preoperative ultrasound at E hospital. Results: mean age was 57.4 ± 16.1; male/female = 1/1.3; 95.3% cholecystitis with gallstones; 100% of chronic cholecystitis had gallstones, gallstones stuck in gallbladder neck accounted for 18.7%; gallbladder wall thickening accounts for 67.2%, in acute cholecystitis, this rate accounts for 90%; Sono-Murphy (+) accounted for 67.2%; in the group of patients with acute cholecystitis, this sign accounts for 95%. Peri-gall bladder fluid accounts for 60% of acute cholecystitis. Value of ultrasound in diagnosis: gallstones Se 100%; Acc 96.9%; PPV 96.7%; stones stuck in gallbladder neck: Se 42.8%; Sp 88%; Acc 78.1%; PPV 50%; NPV 84.6%; gallbladder wall thickness: Se 88.9%; Sp 60.7%, Acc 76.6%; PPV 74.4%, NPV 80.9%; fluid around the gallbladder: Se 82.1%; Sp 94.4%; Acc 89.1%; PPV 92.0%; NPV 87.2%; fat infiltration around the gallbladder: Se 35.7%; Sp 100%; Acc 71.9%; PPV 100%; NPV 66.7%; cholecystitis: Se 70.3%, Acc 70.3%; PPV 70.3%. Conclusion: Ultrasonography is reliable enough in the diagnosis of cholecystitis. Keywords: Cholecystitis, gallstones, ultrasound.